Experiential design for elephant conservation - Shy, Kelsie Danielle (Kansas State University, 2017)
In the past few decades, U.S. cities have seen a rise in animal sanctuaries as an alternative for traditional zoos. These facilities are often seen as more humane because they provide more space and natural surroundings than zoos do. The impact of animal activists and increasing regulations are forcing many zoos to close exhibits for their largest, most expensive animal: the elephant. When these elephant exhibits are closed, the elephants cannot return to the wild. They must be sent to either another zoo, or an elephant sanctuary. As more and more elephants are being retired from zoos, the few sanctuaries in the United States must take on the responsibility of housing them. Elephants are an endangered species, and experience a major threat from poaching and harmful tourism practices. Elephant tourism is one of the most popular industries is southeast Asia, and has led to the use of cruel training techniques. Most people, even those with interest in animals, are unaware of these threats. There are many animal sanctuaries all over the world that use tourism as a way to educate the public and about conservation and raise funds. However, there are few places like this in the United States. Creating a place for elephant based tourism in the U.S. may solve the issue of limited sanctuary space, while providing an opportunity for visitors to learn about elephants and the need for conservation. The landscape architecture profession has an opportunity to contribute to animal sanctuaries because of its knowledge in design, art, science, and the relationship between the built and natural environment. Thoughtful design and functionality is beneficial for a harmonious relationship between visitors, caretakers, and animals. This project proposed a design for an expanded sanctuary at the Ringling Center for Elephant Conservation in Polk City, Florida. This center is currently home to the Ringling Circus’ retired performing elephants. The purpose of this project is to examine how the design of a conservation center can influence visitor experience and promote public conservation efforts for endangered animal populations, specifically the Asian elephant. By studying existing animal attractions, conservation efforts, elephant care resources, and visitor education guidelines, a collective knowledge can be applied to a new conservation center. Methods to support this projected design include: precedent studies, analysis of zoo exhibit design guidelines, financial analysis, and site inventory and analysis. The results of this research give direction to the final design outcome. This project concludes with a new conservation center design that creates unique, interactive experiences between visitors and elephants, while connecting the elephants to an overall message of conservation. A variety of activities cater to all types of visitors and offer fulfilling encounters while adventuring on the site. A multifuncitonal design that utilizes sinuating circulation, vista-like views, cultural materiality, animal enrichment features, and creative safety techniques allows guests to have a visceral experience and ingites an emotional connection towards the elephants, which in turn leads to care for conservation.
Keywords: Elephant; Conservation; Tourism; Ringling; Forida